Joki Nikah Dalam Persepektif Hadis - Ibrahim Ibrahim; Muhammad Alif (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Marriage is taken in a good way to seek the pleasure of Allah SWT, in the journey of household quarrels are something that is certain to exist even in someone who loves each other, quarrels can happen in everyone's household no matter whether the person is rich, famous, intelligent, mature or even a religious figure no one can avoid quarrels, what a husband and wife can do is respond to the conflict well and calmly by not rushing to divorce each other or pronounce a divorce. Religion has provided leniency to be able to reconcile the first and second divorces therefore the husband must be very careful in pronouncing the third divorce which cannot be reconciled which in the end can make someone take the wrong path by paying muhallil and this act is an act that is cursed by Allah SWT and can make someone not get his grace.